Does the coupling of the semiannual oscillation with the quasi-biennial oscillation provide predictability of Antarctic sudden stratospheric warmings? - Nordström, Viktoria J.; Seppälä, Annika (Atmospheric Chemistry and Physics, 2021)
During September 2019 a minor sudden stratospheric warming took place over the Southern Hemisphere (SH), bringing disruption to the usually stable winter vortex. The mesospheric winds reversed and temperatures in the stratosphere rose by over 50 K. Whilst sudden stratospheric warmings (SSWs) in the SH are rare, with the only major SSW having occurred in 2002, the Northern Hemisphere experiences about six per decade. Amplification of atmospheric waves during winter is thought to be one of the possible triggers for SSWs, although other mechanisms are also possible. Our understanding, however, remains incomplete, especially with regards to SSW occurrence in the SH. Here, we investigate the effect of two equatorial atmospheric modes, the quasi-biennial oscillation (QBO) at 10 hPa and the semiannual oscillation (SAO) at 1 hPa during the SH winters of 2019 and 2002. Using MERRA-2 reanalysis data we find that the easterly wind patterns resembling the two modes merge at low latitudes in the early winter, forming a zero-wind line that stretches from the lower stratosphere into the mesosphere. This influences the meridional wave guide, resulting in easterly momentum being deposited in the polar atmosphere throughout the polar winter, decelerating the westerly winds in the equatorward side of the polar vortex. As the winter progresses, the momentum deposition and wind anomalies descend further down into the stratosphere. We find similar behaviour in other years with early onset SH vortex weakening events. The magnitude of the SAO and the timing of the upper stratospheric (10 hPa) easterly QBO signal was found to be unique in these years when compared to the years with a similar QBO phase. We were able to identify the SSW and weak vortex years from the early winter location of the zero-wind line at 1 hPa together with Eliassen–Palm flux divergence in the upper stratosphere at 40–50∘ S. We propose that this early winter behaviour resulting in deceleration of the polar winds may precondition the southern atmosphere for a ...